• 2022-06-01
    下述不是∀x∃yP(x,y)否定的是?
    A: ∀x∀y(﹁P(x,y))
    B: ∃x ∀y (﹁P(x,y))
    C: ∀x∃y(﹁P(x,y))
    D: ∃x ∃y(﹁P(x,y))
  • A,C,D

    内容

    • 0

      下列哪个不是谓词公式() A: ∀x(P(x)→Q(x)) B: ∃z(∀x∃y∨P(z)) C: ∃x(P(x)∧P(y)) D: ∃y(∀x(P(x,y))→∀x(P(x)))

    • 1

      下列哪个不是谓词公式() A: ∀x(P(x)→Q(x)) B: ∃z(∀x∃y∨P(z)) C: ∃x(P(x)∧P(y)) D: ∃y(∀x(P(x,y))→∀x(P(x)))

    • 2

      表达式∀x(P(x,y)∨Q())∧∃y(R(x,y)→∀Zq())中∀x的辖域是() A: P(x,y) B: P(x,y)∨Q(z) C: R(x,y) D: P(x,y)∧R(x,y)

    • 3

      设P(x):x是大象,Q(x):x是老鼠,R(x,y):x比y重,则命题“大象比老鼠重”的符号化为 A: ∀x∀y(P(x)∧Q(y)→R(x,y)) B: P(x)∧Q(y)→R(x,y) C: ∀x∃y(P(x)∧Q(y)∧R(x,y)) D: ∃x∃y(P(x)∧Q(y)∧R(x,y))

    • 4

      下列哪个不是谓词公式() A: ∀x﹁(P(x)→Q(x)) B: ∃y(∀x(P(x,y))→∀x(Q(x))) C: ﹁∃x(P(x)∨P(y)) D: ∃z∀x(∃y∨P(z))